2009
DOI: 10.4049/jimmunol.0803153
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD83 on B Cells Modulates B Cell Function In Vivo

Abstract: The transmembrane glycoprotein CD83 is an important regulator of both thymic T cell maturation and peripheral T cell response. Recent studies suggested that CD83 is also involved in the regulation of B cell maturation, activation, and homeostasis. In this study, we show that in vivo overexpression of CD83 dose dependently interfered with the Ig response to thymus-dependent and thymus-independent model Ag immunization. CD83 deficiency, in contrast, which was restricted to B cells in mixed bone marrow chimeras, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 46 publications
4
37
2
Order By: Relevance
“…The reduced Ig response in total CD83 KO animals can be explained by a strong reduction of CD4 + Th cells, which normally trigger Ig class switch in T cell-dependent immune responses. This is in accordance with findings from bone marrow chimeras using transfer of total CD83 KO bone marrow in WT animals, which show no influence on the humoral responses (13). In contrast, overexpression of CD83 in CD83tg mice led to reduced humoral responses to thymus-dependent and thymus-independent Ags (13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduced Ig response in total CD83 KO animals can be explained by a strong reduction of CD4 + Th cells, which normally trigger Ig class switch in T cell-dependent immune responses. This is in accordance with findings from bone marrow chimeras using transfer of total CD83 KO bone marrow in WT animals, which show no influence on the humoral responses (13). In contrast, overexpression of CD83 in CD83tg mice led to reduced humoral responses to thymus-dependent and thymus-independent Ags (13).…”
Section: Discussionsupporting
confidence: 90%
“…2/2 bone marrow were performed (13). Expression of CD83 on germinal center (GC) lymphocytes was first shown in 1992 (1), and since 2012 it has been used as a marker for light zone (LZ) B cells during GC reactions (14).…”
mentioning
confidence: 99%
“…The possibility of such immune modulation is unknown; however, the differential stimulation requirements of CD11c-positive and CD11c-negative DCs have already been elucidated (28). Modulation of CD83 may also be a potential target, as increased CD83 has been correlated with an increased antibody response in B cells (29) and increased expression of MHC class II and CD86 costimulatory molecules on DCs (60). Similar to our results, the engagement of the CD83 ligand (CD83L) preferentially enriches and significantly amplifies the number of antigenspecific CD8…”
Section: Cd11csupporting
confidence: 85%
“…We and others reported that recombinant sCD83 inhibits DC maturation (28,29) and blocks T cell stimulation (28,30). It has also been reported that CD83 is a regulator of B cell function (31,32).…”
mentioning
confidence: 83%